Direct simulation Monte Carlo method of deposition processes - Tan, Chee Hong. (2008)
Modifications had been done on the basic DSMC2.fortran program developed by G. A. Bird to approximate the initial deposition profile characteristic of a physical vapor deposition process, whereby little or no surface chemical reaction occurs. In this report, initial deposition growth of PVD Aluminum is studied using the number flux distribution along the surface of a 0.6um x 0.6um trench found commonly in a semiconductor device. Existing technical literatures and publications will be used to confirm the validity of the experimental results.